Sleep duration and cognitive function among rural older adults in China: A population-based study - Yongxu Fang; Zhongrui Yan; Xinglu Wang; Rui She; Peng Wang; Yajun Liang (PLoS ONE, 2025)
Background Appropriate sleep duration is essential for maintaining normal cognitive function, but evidence is scarce in rural elderly population. This study aims to determine the associations between sleep duration and cognitive function among older adults in rural China. Methods This population-based cross-sectional study used data from the Confucius Hometown Aging Project in Shandong, China. Data on demographics, lifestyles, and chronic health conditions were collected through questionnaire surveys, clinical examinations, and laboratory tests. Sleep duration per day was classified into four groups (≤5 h, 6 h, 7 h, and ≥8 h). The Mini-Mental State Examination (MMSE) was used to assess the global and domain-specific cognitive function. Linear and logistic regressions were performed to determine the associations between sleep duration and cognitive function. Results Compared with 6 h sleep per day, sleep ≤5 h per day was associated with a higher odd of cognitive impairment with odds ratio (95% confident interval) being 1.70 (1.05, 2.74), but the association was attenuated and insignificant after the adjustment of covariates. Compared to those with 6 h sleep, individuals reporting short (≤5 h) or long (≥ 8 h) sleep duration per day had a lower MMSE score, and the adjusted β coefficient (95% confidence interval) was −0.36 (−0.71, −0.02) for sleep ≤5 h and −0.68 (−1.06, −0.30) for sleep ≥8 h. The patterns were similar for cognitive subdomains in orientation, attention and calculation. Conclusions Our study showed that abnormal sleep duration was associated with poor cognitive function in older adults in China. Specifically, longer or shorter sleep duration was associated with lower cognitive function.